Major bleeding events after endoscopic sphincterotomy and endoscopic papillary balloon dilatation in cirrhotic patients: A nationwide population‐based cohort study. Issue 1 (31st March 2017) - Wang, Chi‐Chih; Tsai, Ming‐Chang; Tseng, Ming‐Hseng; Yang, Tzu‐Wei; Wang, Yao‐Tung; Lin, Chun‐Che
Summary: Backgrounds and aims: Endoscopic sphincterotomy (EST) or endoscopic papillary balloon dilatation (EPBD) were two important methods for therapeutic endoscopic retrograde cholangiopancreatography (ERCP). Post‐ERCP bleeding is a troublesome issue especially in patients with bleeding tendency, like cirrhotic patients. In viewing the need of a safer method, we thus aimed to evaluate the post‐EST or post‐EPBD bleeding rate among cirrhotic patients based on Taiwan's National Health Insurance Research Database (NHIRD). Methods: As per one million population data selected from NHIRD, patients who were hospitalized or accessing outpatient clinics for 3 times with a primary diagnosis of liver cirrhosis (ICD‐9 codes 571.2 and 571.5) between January 1, 2004 and December 31, 2011, were collected as research subjects. Rates of major gastrointestinal tract bleeding events appeared within 14 days after EST or EPBD in both cirrhosis and non‐cirrhosis patients were compared. Results: A total of 1852 patients, age above 18 years old without end stage renal disease, accepted total 2132 EST or EPBD procedures during the sampling period picked. EST was adopted much more often than EPBD not only in cirrhotic patients (154 vs. 15 events), but also in non‐cirrhotic patients (1793 vs. 170 events). Post‐EST bleeding events occurred more frequently in cirrhotic patients than in non‐cirrhotic patients (4.55% vs. 2.12%; p = 0.119). Post‐EPBD bleeding events were similar in both groups (0.00% vs. 0.59%; p > 0.999). Post‐EST bleeding rate was higher than post‐EPBD bleeding rate in both non‐cirrhotic patients (2.12% vs. 0.59%; p = 0.269) and cirrhotic patients (4.55% vs. 0.00%; p > 0.999), although results did not meet the significant statistical difference in our study. Conclusions: In contrast to EST, EPBD showed fewer post‐EPBD major bleeding events especially in cirrhotic patients. Thus EPBD tend to be a relative safer method of therapeutic ERCP especially for cirrhotic patients. Copyright © 2017, The Gastroenterological Society of Taiwan, The Digestive Endoscopy Society of Taiwan and Taiwan Association for the Study of the Liver.